Health insurance, endogenous medical progress, and health expenditure growth - Ivan Frankovic; Michael Kuhn (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2018)
We study the impact of health insurance expansion in the US on health expenditure, longevity growth and welfare in an overlapping generations economy in which individuals purchase health care to lower mortality. We consider three sectors: final goods production; a health care sector, selling medical services to individuals; and an R&D sector, selling increasingly effective medical technology to the health care sector. We calibrate the model to match the development of the US economy/health care system from 1965 to 2005 and study numerically the impact of the insurance expansion on health expenditures, medical progress and longevity. We find that more extensive health insurance accounts for a large share of the rise in US health spending but also boosts the rate of medical progress. A welfare analysis shows that while the moral hazard associated with subsidized health care creates excessive health care expenditure, the gains in life expectancy brought about by induced medical progress more than compensate for this. By mitigating an intergenerational externality associated with the longevity benefits from current medical innovation the expansion of health insurance constitutes a Pareto improvement.
Keywords: D15; I11; I12; I18; J11; J17; O31; O41; 330; life-cycle model; health care spending; health insurance; medical progress; moral hazard; overlapping generations